Editor's Note: Advocates Make a Difference for Transparency - David Cuillier (The Journal of Civic Information, 2022)
It takes dedicated volunteers, like Charles N. Davis, and nonprofit groups to push for transparency in government and civic information, as demonstrated by those who challenge secret holds within the U.S. Senate. Also to be acknowledged is Frank LoMonte, who founded this journal through the Brechner Center for Freedom of Information, and now moves on to advocate for civic information as legal counsel for CNN.